6......................................... i mean this is probably wrong but yeah
Answer:
x = (-5 ± 2√10) / 3
Step-by-step explanation:
5 − 10x − 3x² = 0
Write in standard form:
-3x² − 10x + 5 = 0
Solve with quadratic formula:
x = [ -b ± √(b² − 4ac) ] / 2a
x = [ -(-10) ± √((-10)² − 4(-3)(5)) ] / 2(-3)
x = [ 10 ± √(100 + 60) ] / -6
x = (10 ± 4√10) / -6
x = (-5 ± 2√10) / 3
24 divided by 80= 0.3
24/30 there were 30 questions on the test and he got 24 right
Answer:
x = 2
Step-by-step explanation:
11+3 = 9x-2x
14 = 7x
x = 14/7
x = 2
Hope I helped! :)))